Protein structure controls the processing of the N-linked oligosaccharides and glycosylphosphatidylinositol glycans of variant surface glycoproteins expressed in bloodstream form Trypanosoma brucei - Zitzmann, N; Mehlert, A; Rudd, P; Ferguson, M; Carrouée, S (Oxford University Press, 2000)
The variant surface glycoproteins (VSGs) of Trypanosoma brucei are a family of homodimeric glycoproteins that adopt similar shapes. An individual trypanosome expresses one VSG at a time in the form of a dense protective monolayer on the plasma membrane. VSG genes are expressed from one of several polycistronic transcription units (expression sites) that contain several expression site associated genes. We used a transformed trypanosome clone expressing two different VSGs (VSG121 and VSG221) from the same expression site (that of VSG221) to establish whether the genotype of the trypanosome clone or the VSG structure itself controls VSG N-linked oligosaccharide and GPI anchor glycan processing. In-gel release and fluorescent labeling of N-linked oligosaccharides and on-blot fluorescent labeling and release of GPI anchor glycans were employed to compare the carbohydrate structures of VSG121 and VSG221 when expressed individually in wild-type trypanosome clones and when expressed together in the transformed trypanosome clone. The data indicate that the genotype of the trypanosome clone has no effect on the N-linked oligosaccharide structures present on a given VSG variant and only a minor effect on the GPI anchor glycans. The latter is most likely an effect of changes in inter-VSG packing when two VGSs are expressed simultaneously. Thus, N-linked oligosaccharide and GPI anchor processing enzymes appear to be constitutively expressed in bloodstream form African trypanosomes and the tertiary and quaternary structures of the VSG homodimers appear to dictate the processing and glycoform microheterogeneity of surface-expressed VSGs.